FORMULATING A SHARIA-BASED LEGAL FRAMEWORK FOR SWIMMING POOL OPERATIONS IN INDONESIA - Parman Komarudin; Ilham Akbar; Muhamad Rahmani Abduh; Muhammad Rifqi Hidayat; Muhammad Hendri Yanova (Universitas Nurul Jadid, 2026)
The need of Muslim communities for swimming facilities that uphold modesty requirements (awrah), regulate gender interaction (ikhtilāṭ), ensure privacy, and support religious observance has not been fully accommodated in the operation of swimming pools in Indonesia. This issue reflects not only the absence of a specific fatwa concerning Sharia-compliant swimming pools but also the lack of a Sharia governance standard for water-based recreational facilities. This study aims to develop a normative academic framework for the operation of swimming pools based on Sharia principles in Indonesia. This research employs a normative Islamic legal approach, utilizing statutory, conceptual, maqāṣid-based, and fatwa approaches. Data were collected through a literature review of Islamic legal sources, fatwas issued by the National Sharia Council of the Indonesian Council of Ulama (DSN-MUI), environmental health regulations, and halal tourism literature. The findings demonstrate that a Sharia-compliant swimming pool should be constructed through three principal dimensions: the normative-religious dimension, the operational-managerial dimension, and the environmental health and safety dimension. These dimensions are grounded in fiqh al-muʿāmalāt, maqāṣid al-sharīʿah, and public health standards, particularly with respect to the protection of religion, life, and human dignity. This study contributes by proposing an academic framework of Sharia norms encompassing definitions, legal status, operational principles, user regulations, privacy protection, facility standards, contractual arrangements, supervisory mechanisms, and complaint-handling procedures. The proposed framework is not intended to serve as an official fatwa; rather, it is designed to provide an academic foundation for fatwa-issuing institutions, regulators, and operators of water-based recreational facilities in formulating standards for swimming pools based on Sharia principles.